OS9.7 Telomere length, TERTp mutation and ALT status in adult diffuse gliomas. (6th September 2019) - Birzu, C; Hillairet, A; Giry, M; Grandin, N; Verrelle, P; Mokhtari, K; Marie, Y; Hoang-Xuan, K; Delattre, J; Idbaih, A; Charbonneau, M; Sanson, M; et al.
Abstract: BACKGROUND: The current classification of adult diffuse gliomas integrates two alternative telomere maintenance mechanisms: reactivation of telomerase activity by TERT promoter ( TERT p) mutations or ATRX mutations associated with alternative length telomere (ALT). We investigated here the relation between these two mechanisms, telomere length, and outcome in a large series of diffuse gliomas. MATERIAL AND METHODS: We performed C-circle assay (CCA) to determine ALT status, determined telomere length in tumor (RTLt) and leukocyte (RTLl) in a cohort of 354 adult diffuse gliomas, and sequenced ATRX gene. We calculated an age-adjusted telomere score considering tumor and leukocyte (blood) telomere length and corrected by age. This score was used in univariate and multivariate survival analyses to evaluate the potential impact of telomere length on the prognosis of gliomas. We used the TCGA LGG-GBM dataset to validate our findings in an independent cohort. RESULTS: RTLl and RTLt were associated with ATRX mutation and ALT phenotype, and negatively associated with age and TERT p mutations. ATRX mutations (found in 52% (64/123) of samples) were mostly transitions (C>T or T>C), and were associated with ALT phenotype. None of 1p/19q co-deleted oligodendrogliomas harbored an ALT phenotype. No patients with TERT p mutations had ALT phenotype except for a very small subgroup of patients (3/87, 3.4%) suggesting that multiple ways of telomere maintenance, may co-exist in a single tumor, probably expressed in different clones. Telomere age-adjusted score was independently associated with better outcome (HR= 0.73 [95% CI 0.56–0.97], p-value 0.03 adjusted for age, TERT p mutation, IDH mutation, 1p/19q co-deletion and WHO grade). These results were validated using the LGG-GBM TCGA dataset. CONCLUSION: We unravel the relation between RTLl and RTLt, TERTp mutation and ALT phenotype and describe a novel telomere age-adjusted score independently associated with better prognosis in adult diffuse gliomas.